DUOLINGO : AN APP TO BOOST STUDENTS' VOCABULARY IN SPEAKING - Meliyuana, Putri; Suryani, Suryani; Dauyah, Ema (Jurnal Dedikasi Pendidikan, 2025)
The purposes of this study are to determine the improvement and perception of students about the use of the Duolingo application as an English learning tool. This research uses quantitative method. The sample of this study was 22 students in IPAS-3 class of the academic year 2023/2024. Data was obtained through the collection of test results and distribution of questionnaires. The test contains one topic about "family", while the questionnaire contains 10 closed questions. Based on data analysis of test, students' vocabulary skills in speaking have improved. Before the treatment, students' vocabulary ability in speaking had an average score 36.82, while after the treatment, students' vocabulary ability in speaking improved as much as 65,45. In addition, based on the questionnaire data, it was revealed that there are 4 very high categories, namely Duolingo is easy to use for beginners (83%), animated displays on Duolingo can attract attention (83%), students are excited to learn English through the Duolingo application (83%), and this application can help students learn English (85.2%). It is suggested that teachers can use Duolingo aplication in the teaching of vocabulary for speaking purposes.